Aminoglycoside resistance dynamics and its predictive value for carbapenem resistance in multidrug-resistant Acinetobacter baumannii and Klebsiella pneumoniae - Bence Sajerli; Klára Makai; Lóránt Lakatos; Ágnes Sarkadi-Nagy; Katalin Burián; László Orosz (Journal of Global Antimicrobial Resistance, 2025)
Objective: The rise of multidrug-resistant bacterial pathogens, including carbapenem-resistant Acinetobacter baumannii (CRAB) and Klebsiella pneumoniae (CRKP), poses a global healthcare challenge. Aminoglycosides remain among the few effective therapeutic options, but increasing resistance threatens their efficacy. This study investigates aminoglycoside consumption and resistance dynamics, focusing on the predictive value of aminoglycoside resistance for future carbapenem resistance. Methods: Data on aminoglycoside use (amikacin, gentamicin, tobramycin) and resistance were retrospectively collected (2010–2024). Resistance patterns were assessed using the antibiotic resistance index and resistance instability index. Correlation analyses examined associations between aminoglycoside consumption and resistance, including delayed effects, and between aminoglycoside and meropenem resistance. Results: We analysed 4582 A. baumannii and 36 049 K. pneumoniae isolates. Among them, 2462 CRAB and 309 CRKP isolates were identified. Amikacin was the most used aminoglycoside, with stable resistance in CRAB and higher variability in CRKP. Gentamicin showed the most unstable resistance. In CRAB, aminoglycoside resistance – especially amikacin (r = 0.73) – was strongly correlated with meropenem resistance, suggesting predictive potential. In CRKP, predictive correlations were weaker; gentamicin showed the highest (r = 0.62). Conclusions: Aminoglycoside resistance trends, particularly for amikacin in CRAB, may serve as early indicators of emerging carbapenem resistance. Integrating such data into surveillance and stewardship frameworks could improve early detection and response to multidrug-resistant threats.